Comparative Analysis of Steel Structure with Rigid and Semi Rigid Joints Using Analysis Tool ETABS - Chandrakanta Patel; Shiva Verma; Lokesh Singh (International Journal of Scientific Research in Civil Engineering, 2025)
Generally, in steel structure the connection between beam and column are designed as moment connection and pinned connection, but in actual condition the structure behaves between these two conditions, resulted into semi-rigid condition which is intermediate stage between rigid and pinned joints. Effect of semi-rigid connection on multi-story multi-bay frame is accomplished in this paper. The present study introduces the effect of static and dynamic loading on high rise steel structure of G+12 story with 4m, 6m and 8m three bay span length. Structure is analyzed under two different condition of partial release of semi-rigid connections which is derived by fixity factor of values 0.5 and 0.75 in this study. The analysis is done commercially available software ETABS. From the non-linear analysis, the story displacement and story drift are obtained. The overall performance of the structure from the analysis, semi-rigid joints display more story displacement and story drift compared to rigid joints. To overcome the results, bracing system is introduced at different location of periphery of structure. These brace frame structure consist of X- bracing and diagonal bracing. Again, comparative analysis is to be performed in ETABS on these three-bay span lengths. It is found that braced semi-rigid frame structure perform quite well as compared to unbraced frame structure.